EXPLORING THE ROLE OF FAMILY INVOLVEMENT IN SUPPORTING PHYSICAL ACTIVITY AMONG CHILDREN WITH DISABILITIES: EARLY RESULTS - Sanja Selimović; Stanko Blatnik; Gina Škulić; Luka Dobrović (Research in Education and Rehabilitation, 2025)
Train4Inclusive is a European initiative co-funded by the Erasmus+ Programme, designed to promote physical activity among children with disabilities aged 6 to 18, by involving family members in sport education and organized activities. This article presents an overview of the project, its objectives, methodology, and preliminary findings based on a Likert-scale survey conducted after five months of implementation across seven partner countries. Results show significant improvements in physical coordination, water confidence, social interaction, and parental engagement, underscoring the importance of a holistic, family-centered approach to physical development and inclusion. There is limited research on structured physical activity programs, especially swimming, where children with disabilities train together with their parents. This study contributes to filling that gap.